Edukasi Etika Bermedia Sosial untuk Para Siswa di SMK Ananda Bekasi - Tatik Purwaningsih; Ria Restina Robiyanti; Arnold Surya Nugroho (Jurnal Pengabdian Masyarakat Waradin, 2024)
The development of information technology in this era has had quite a big impact throughout the world on changes in various fields. One form of technological development is the birth of social media. Social media has an influence on shifts and changes in people's behavior and life in terms of ethics, norms and culture. There are various impacts of social media, both positive and negative impacts. To be able to prevent negative impacts or negative impacts from occurring, an in-depth understanding of good ethics in communicating on social media is needed. This research aims to increase the understanding of Ananda Bekasi Vocational School students about social media ethics through a systematic educational program. With the rapid development of information and communication technology, the use of social media among teenagers is increasingly widespread, but is often accompanied by unethical behavior. The methods used in this research include seminars, interactive discussions, and creating positive content. The activity was attended by 260 students, and the results showed a significant increase in ethical awareness of social media, from 60% to 85% after the program. Participant responses showed high enthusiasm, with 96% finding this activity useful. Apart from that, students succeeded in creating various content that was educational and inspiring. This research emphasizes the importance of social media ethics education as a proactive step in forming positive behavior among teenagers, especially students at Ananda Bekasi Vocational School, and recommends implementing similar programs on an ongoing bas